Humeral retroversion, corrected range-of-motion, and fast scores in collegiate baseball pitchers - Hoskins, T.; Christensen, B.; Gange, K.; Collins, K.; Smith, J. (ISBS Proceedings Archive (Michigan), 2023)
The purpose of this study was to examine the relationship between shoulder rotational range of motion, accounting for humeral retroversion (HR) and the Functional Arm Scale for Throwers (FAST). Nineteen male NCAA Division I collegiate baseball pitchers participated in the study and completed a modified FAST form. Humeral retroversion was measured and total rotational range of motion, corrected internal rotational range of motion, and corrected external rotational range of motion were calculated. No relationships were found between rotational ROM and the FAST score. The findings suggest further research needs to be performed on patient reported outcomes specific to changes in rotational ROM.